Perlindungan Hukum Hak Kekayaan Intelektual dalam Ekonomi Digital: Tantangan Penegakan Hak Cipta dan Merek di Indonesia: Penelitian - Urbanisasi; Daniel Reynaldi L Tobing (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid growth of the digital economy has significantly transformed the creation, distribution, and use of intellectual works, creating substantial challenges for the protection and enforcement of Intellectual Property Rights (IPR) in Indonesia. This study examines two major issues: (1) the legal protection framework for copyright and trademarks within the digital economic landscape, and (2) the effectiveness of enforcement mechanisms against digital IPR infringements, along with key implementation obstacles. Copyright and trademark protections are governed by Indonesia’s Copyright Law and Trademark Law, strengthened by international standards such as TRIPs and the WIPO Internet Treaties. Enforcement mechanisms include criminal, civil, and administrative actions, as well as government-led digital access termination. However, their effectiveness remains limited due to technological complexities, low IPR literacy, slow platform responses, insufficient digital forensic capabilities, and cross-border jurisdictional barriers. This study highlights that robust IPR protection in the digital era requires regulatory harmonization, improved enforcement capacity, and strong collaboration among the government, rights holders, and digital platforms.